2016
DOI: 10.5152/dcbybd.2016.818
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Central Venous Catheterization Complications and Related Risk Factors in a Pediatric Intensive Care Unit

Abstract: Objective: In this study, we aimed to evaluate central venous catheter insertion related complications and related risk factors in a pediatric intensive care unit. Material and Methods:All patients hospitalized between 17.10.2012 and 24.08.2014 in a pediatric intensive care unit were included in the study. Central venous catheterization patients in terms of age, sex, cause of catheter insertion, and removal, depending on catheter interventions, were evaluated in terms of developing complications and risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A prospective study performed in 29 NICU in the United States and found that the risk of CLABSI is very low during the first week of catheterization and especially with lines inserted in the jugular vein (12,16) . In the study conducted by Ergul et al (17) , it was determined that CLABSI incidence increased with the catheter duration. Similarly in our study, there was a relation between CLABSI and catheter duration days, femoral catheters, and three-lumen catheters.…”
Section: Discussionmentioning
confidence: 98%
“…A prospective study performed in 29 NICU in the United States and found that the risk of CLABSI is very low during the first week of catheterization and especially with lines inserted in the jugular vein (12,16) . In the study conducted by Ergul et al (17) , it was determined that CLABSI incidence increased with the catheter duration. Similarly in our study, there was a relation between CLABSI and catheter duration days, femoral catheters, and three-lumen catheters.…”
Section: Discussionmentioning
confidence: 98%
“…Infection is also a common cause of catheter removal. 1 In our study, a CRBSI was the second most common cause of removal (after elimination of the need for a catheter). No significant difference in terms of the causes of catheter removal was evident between the groups.…”
Section: Discussionmentioning
confidence: 61%
“…Catheter-Related Bloodstream Infections (CRBSIs) are frequent complications of catheterization. 1 In the USA, approximately 80,000 CRBSIs develop annually in ICUs, with mortality rates of up to 35%. 2 Several strategies are employed to reduce CRBSIs; these include skin antisepsis, prescription of prophylactic antibiotics, the use of antimicrobial catheters, implementation of catheter care bundles, chlorhexidine baths, and addition of antimicrobials (in the form of antimicrobial locks or dressings) to catheters.…”
Section: Introductionmentioning
confidence: 99%
“…Central venous catheters (CVC) is a procedure in which a catheter with various specifications is inserted into a central vein leading directly to the heart (Bell, & O'Grady, 2017;Ergül et al, 2016). CVC can be used for different purposes in each patient.…”
Section: Introductionmentioning
confidence: 99%